Management of Pressure Gauge Usage on Tires to Increase Pressure Gauge Cost Efficiency and Pressure Gauge Maintenance at PT Antareja Mahada Makmur MIFA Site for the Period April – July 2025 - Rizkiawan, Muhammad Afif; Trikomara, Reka (International Journal of Social Service and Research, 2025)
Proper pressure gauge management is crucial in maintaining tire performance and extending tire lifespan, as incorrect tire pressure—especially underinflation—can significantly shorten service life and lead to tire blowouts. In industrial and mining operations, where tire replacement costs are high, effective monitoring of tire pressure using well-maintained gauges becomes an essential aspect of preventive maintenance. This study aims to evaluate and implement an effective pressure gauge management system to ensure accurate tire pressure monitoring and reduce equipment damage due to improper maintenance. The method used in this study involved direct observation and data collection on gauge usage, routine calibration schedules, and the cleaning process of gauges across several operational units. Regular calibration and proper cleaning techniques were introduced to improve tool reliability and minimize the risk of inaccurate readings caused by dust accumulation. The results showed that after the implementation of systematic gauge management, the company achieved cost savings of approximately IDR 30,120,000, representing a significant 15% improvement in maintenance efficiency through reduced tool replacement and scrap rates. The implications of this research highlight that structured gauge management programs not only enhance safety and operational reliability but also provide a sustainable model for industrial maintenance systems, particularly in sectors with high equipment utilization such as mining, transportation, and heavy manufacturing.